Efficient detoxification of corn cob hydrolysate with ion-exchange resins for enhanced xylitol production by Candida tropicalis MTCC 6192. (March 2018) - Kumar, Vinod; Krishania, Meena; Preet Sandhu, Pankaj; Ahluwalia, Vivek; Gnansounou, Edgard; Sangwan, Rajender S.
Graphical abstract: Highlights: Utilization of secondary agricultural wastes for xylitol production after nitric acid hydrolysis followed by resin treatments. Efficient and effective process for detoxification of corn cob acid hydrolyzed. The xylitol production was improved by the detoxified corn cob acid hydrolyzed. Abstract: The present study demonstrates utilization of secondary agricultural wastes for xylitol production. The highest xylan-to-xylose (70%) conversion was achieved using dilute nitric acid as catalyst followed by resin treatment. Results show that resin treatment efficiently removed nitrate salt (70%), phenolic content and 5-HMF (70%). Highest xylitol yield (85%) was achieved during fermentation using Candida tropicalis MTCC 6192 from the neutralized hemicellulosic hydrolysate medium. Good recovery (>15%) was achieved from corncob with 85% xylose to xylitol conversion during fermentation. This two-step process for transformation of agri-waste to xylitol is much simpler and it could possibly be considered for up scaling after process optimization parameters.